Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.

The Role of Music in the Quebec Sephardic Community - Cohen, Judith R. (Contemporary Sephardic Identity in the Americas: An Interdisciplinary Approach, 2012)

Introduction : la voix d’Ana Sokolović - Goldman, Jonathan (Circuit, 2012)

Musical Robots and the Serbian Kolo: A Narrative Analysis of Ana Sokolović’s Géométrie sentimentale (1997) - Harman, Brian (Circuit, 2012)
Composer Ana Sokolović divided her instrumental work Géométrie sentimentale into large sections inspired by pure geometric shapes — Triangle, Cercle and Carré — describing these sections as three contrasting perspectives of the same musical materials. This article uses a narrative analytical approach as a lens through which to understand these distinct sections and the materials populating them. Inspired by Sokolović’s employment of musical objects in her compositions and by the extra-musical concepts inspiring many of her works, this analysis uses a collection of colourful robot toys as metaphors for the work’s materials. Three unique perspectives of these toys are described: in Triangle, the robots interact as characters on a dramatic stage; in Cercle, they peacefully coexist in slow motion; and in Carré new combinations of robot elements are abruptly juxtaposed against each other. The characteristics and interactions between these toys, as well as the various harmonic ‘masks’ that the composer has them wear, are helpful in understanding Sokolović’s harmonic structure, variation/transformation techniques, formal organization and rhythmic characteristics. The Serbian kolo is also shown as influential on the work, relating directly to the physicality and kinetics of the metaphorical robots.

El cancionero judeoespañol en transición: Un estudio de dos compilaciones de mujeres sefarditas del siglo XX [Le répertoire de chansons judéo-espagnoles en transition : étude de deux compilations de femmes sépharades du XXe siècle] - Havassy, Rivka (Ladinar, 2012)

Musique, immigration et intégration au Québec - Leyssieux, Florence (Université de Montréal, 2012)

Cartographie de l’apprentie - Messier, Anne (Circuit, 2012)
La compositrice québécoise Ana Sokolović est d’origine serbe et plusieurs de ses oeuvres font référence à son pays d’origine, que ce soit par l’utilisation de mélodies et de rythmes traditionnels ou par des références culturelles. Pour approfondir son héritage serbe, l’auteure s’est entretenue avec la compositrice en mars 2012. L’article relate les paysages de son enfance et de son adolescence, l’environnement musical, culturel et politique de ses années d’apprentissage. Le portrait de sa vie familiale et de son quotidien nous permet de saisir des éléments constituants de sa personnalité d’artiste en devenir. Sa décision de s’établir à Montréal est explorée et elle raconte comment elle a pris conscience de son héritage slave.

« J’aime quand on explose de joie ! » : entretien avec Ana Sokolović - Panneton, Isabelle (Circuit, 2012)
Lors d’un entretien réalisé par la compositrice Isabelle Panneton, Ana Sokolović discute de ses inspirations, de ses méthodes et de son rapport avec les interprètes de sa musique.